Evaluation of possible head injuries ensuing a cricket ball impact. (May 2018) - Mohotti, Damith; Fernando, P.L.N.; Zaghloul, Amir
Highlights: The effectiveness of standard cricket helmet in mitigating head injuries is assessed. An experimental program and numerical simulations were performed. A 3D printed head model was used for the experimental program. Head acceleration, pressure, and energy are compared to various acceptance criteria. Pressure film results showed a 60% reduction in the impact pressure with the helmet. Abstract: Background and objective: The aim of this research is to study the behaviour of a human head during the event of an impact of a cricket ball. While many recent incidents were reported in relation to head injuries caused by the impact of cricket balls, there is no clear information available in the published literature about the possible threat levels and the protection level of the current protective equipment. This research investigates the effects of an impact of a cricket ball on a human head and the level of protection offered by the existing standard cricket helmet. Method: An experimental program was carried out to measure the localised pressure caused by the impact of standard cricket balls. The balls were directed at a speed of 110 km/h on a 3D printed head model, with and without a standard cricket helmet. Numerical simulations were carried out using advanced finite element package LS-DYNA to validate the experimental results. Results: The experimental and numerical results showed approximately a 60% reduction in the pressure on the head model when the helmet was used. Both frontal and side impact resulted in head acceleration values in the range of 225–250 g at a ball speed of 110 km/h. There was a 36% reduction observed in the peak acceleration of the brain when wearing a helmet. Furthermore, numerical simulations showed a 67% reduction in the force on the skull and a 95% reduction in the skull internal energy when introducing the helmet. Conclusions: (1) Upon impact, high localised pressure could cause concussion for a player without helmet. (2) When a helmet was used, the acceleration of the brain observed in the numerical results was at non-critical levels according to existing standards. (3) A significant increase in the threat levels was observed for a player without helmet, based on force, pressure, acceleration and energy criteria, which resulted in recommending the compulsory use of the cricket helmet. (4) Numerical results showed a good correlation with experimental results and hence, the numerical technique used in this study can be recommended for future applications.